2013
DOI: 10.1080/03602559.2013.798817
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biodegradable Polylactide/Poly(butylene succinate) Composites via Cross-Linking with Methylene Diphenyl Diisocyanate

Abstract: A novel polylactide/poly(butylene succinate) composite via cross-linking with methylene diphenyl diisocyanate was used. The methylene diphenyl diisocyanate (MDI) was to couple with end hydroxyl of polylactide and poly(butylene succinate) by a torque rheometer and the samples were compression molded into plate successfully. A series of composites was studied with various amounts of poly(butylene succinate) (PBS) from 0 to 40 wt%. Tensile test results demonstrated that the elongation at break of the MDI-based PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…They must be distributed at a high rate in the polymer melt during blending [28]. A large number of reactive compatibilizers for PLA/PBS blends have been reported, for example diphenyl diisocyanate (MDI) [46], lysine triisocyanate (LTI) [42], lysine diisocyanate (LDI) [42], glycidyl methacrylate (GMA) [47], dicumyl peroxide (DCP) [16,44,48], benzoyl peroxide (BPO) [43], organoclays and epoxy functionality-containing components [49], epoxy functionality-containing components (Joncryl TM ) [24].…”
Section: Toughness Modificationmentioning
confidence: 99%
“…They must be distributed at a high rate in the polymer melt during blending [28]. A large number of reactive compatibilizers for PLA/PBS blends have been reported, for example diphenyl diisocyanate (MDI) [46], lysine triisocyanate (LTI) [42], lysine diisocyanate (LDI) [42], glycidyl methacrylate (GMA) [47], dicumyl peroxide (DCP) [16,44,48], benzoyl peroxide (BPO) [43], organoclays and epoxy functionality-containing components [49], epoxy functionality-containing components (Joncryl TM ) [24].…”
Section: Toughness Modificationmentioning
confidence: 99%
“…Based on these aspects, in situ reactive processing can be introduced and applied for hybrid composite processing, allowing the possibility of increasing the interfacial adhesion with a cost-effectiveness in terms of the manufacturing technique [ 10 ]. Some of the current in situ compatibilizers used for each biopolymer blends have been investigated, such as Methylene diphenyl diisocyanate (MDI) used in Poly(lactic acid)/Polybutylene succinate [ 18 ] and Poly( l -lactic acid)/Polycaprolactone [ 19 ], Dicumyl peroxide (DCP) used in Poly( l -lactic acid)/Polybutylene succinate [ 20 ] and PHB/Polybutylene succinate [ 21 ], Joncryl used in Poly(lactic acid)/PBSA [ 22 ], Poly(lactic acid)/Polypropylene carbonate [ 23 ] and Poly( l -lactic acid)/PBAT [ 24 ], PLA-g-GMA (glycidyl methacrylate grafted Poly(lactic acid) used in PLA/Starch [ 25 ], PLA-g-MA (Maleic anhydride-grafted Poly(lactic acid)) used in Poly(lactic acid)/Polycaprolactone [ 26 ], Poly(lactic acid)/Starch [ 27 ] and Poly( l -lactic acid)/Polybutylene adipate terephthalate [ 28 ]. From our previous work, different types of reactive agents including multifunctional epoxide-based reactive terpolymer (CEGMA, EAGMA) and maleic anhydride-based reactive terpolymer (EAMAH) were introduced as in situ reactive compatibilizer in the processing of PLA biocomposites [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 Another possibility to improve the mechanical properties of PLA is polymer blending with the poly(butylene succinate) (PBS) -another bio-based polyester displaying higher flexibility. [13][14][15][16][17][18] Initially, PLA and PBS were reported to be miscible in the amorphous regions, 13 but further studies concluded that phase-separation occurs if the PBS content exceeds 20 wt%. 14 Therefore, multiple efforts have been undertaken on the compatibilization of the two polyesters via reactive blending.…”
mentioning
confidence: 99%
“…14 Therefore, multiple efforts have been undertaken on the compatibilization of the two polyesters via reactive blending. [15][16][17] However, physical blending in presence of an interfacial compatibilizer still represents a more convenient, lower cost and compositioncontrolled method. 18 This blending often uses carefully engineered block or graft copolymers; 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 although another category of interfacial agents has been approached, i.e.…”
mentioning
confidence: 99%